2019
DOI: 10.1002/aqc.3215
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the efficacy of small‐scale marine protected areas for preserving reef health: A case study applying emerging monitoring technology

Abstract: 1. Marine Protected Areas (MPAs) are widely used as management tools to conserve species and ecosystems at risk from human impact. Coastal managers often focus MPA designation on biogenic reef environments due to their value and sensitivity to damage. However, difficulties in enforcement and a lack of capacity to adequately monitor MPAs often make it hard for managers to assess the effectiveness of MPAs, particularly in under-resourced, low-income coastal countries. 2. Reef community data were collected at thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 97 publications
(111 reference statements)
1
22
0
Order By: Relevance
“…Changes in coral cover through time at the site level were only significant at Bilangbilangan (seeing a significant increase in cover inside the MPA) and Pandanon (seeing a Coral Reefs significant decrease in cover inside the MPA). These observations match well to other studies of this reef system which found Bilangbilangan to be relatively well managed, whereas Pandanon was seen to have regular systematic blast fishing occurring (even inside the MPA limits at points in the reserve's history), causing loss of structure and a hampered recovery due to the resultant mobile rubble substrate (Samoilys et al 2007;Bayley et al 2019).…”
Section: Management Implicationssupporting
confidence: 89%
See 4 more Smart Citations
“…Changes in coral cover through time at the site level were only significant at Bilangbilangan (seeing a significant increase in cover inside the MPA) and Pandanon (seeing a Coral Reefs significant decrease in cover inside the MPA). These observations match well to other studies of this reef system which found Bilangbilangan to be relatively well managed, whereas Pandanon was seen to have regular systematic blast fishing occurring (even inside the MPA limits at points in the reserve's history), causing loss of structure and a hampered recovery due to the resultant mobile rubble substrate (Samoilys et al 2007;Bayley et al 2019).…”
Section: Management Implicationssupporting
confidence: 89%
“…Any differences in cover were instead largely driven through site-level heterogeneity. The fishing methods in this localised region therefore appear to typically not be permanently damaging to the benthos, unless intensive localised blast fishing is employed, such as at the site 'Pandanon' within this study (Selgrath et al 2018;Bayley et al 2019).…”
Section: Benthic Community Compositionmentioning
confidence: 94%
See 3 more Smart Citations